Mechanical properties of PLA specimens obtained by additive manufacturing process reinforced with flax fibers - Paulo, Ana (2023)
Abstract Although polylactic acid (PLA) is one of the most used materials in additive manufacturing, its mechanical properties are quite limiting for its practical application, therefore, to improve these properties it is frequent to add fibers and, in this way, create a more resistant composite material. In this paper, the authors developed PLA composites reinforced with flax fibers to evaluate the improvement of tensile and flexural strength. The experimental design of experiments was based on the L18 Taguchi array where the control factors were the extruder temperature (three levels), number of strands (three levels), infill percentage of the specimens (three levels), and whether the flax fiber had surface chemical treatment. The tensile and flexural specimens were made on a 3D printing machine and was a mold was developed to fix and align the fiber strands during the printing process. The tensile and flexural experimental tests were performed in agreement with ASTM D638.14 and ISO 14125 standards, respectively. Analyzing the results, it was verified that the surface chemical treatment (NaOH) of the fiber did not show any influence in the mechanical properties of the composites; in contrast, the infill density demonstrated a huge influence for the improvement of mechanical strength. The maximum values of tensile and bending stress were 50 MPa and 73 MPa, respectively. The natural fiber reinforcement can improve the mechanical properties of the PLA composites.